2002
DOI: 10.1093/glycob/12.5.339
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the mono- and tetrasialogangliosides GM1 and GQ1b on ATP-induced long-term potentiation in hippocampal CA1 neurons

Abstract: The effects of the mono- and tetrasialogangliosides, GM1 and GQ1b, on ATP-induced long-term potentiation (LTP) were studied in CA1 neurons of guinea pig hippocampal slices. Application of 5 or 10 microM ATP for 10 min resulted in a transient depression followed by a slow augmentation of synaptic transmission, leading to LTP. LTP induced by treatment with 5 microM ATP was facilitated in hippocampal slices prepared from animals treated for 6 days with a ceramide analog, L-threo-1-phenyl-2-decanoylamino-3-morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 26 publications
2
23
0
Order By: Relevance
“…Since activation of CaMKII due to Ca 2+ influx through NMDA receptors is involved in the mechanism of LTP in hippocampal CA1 neurons, but not in the mechanism of LTD, it is possible that inhibition of de novo synthesis of b-pathway gangliosides in d-PDMP-treated mice decreases CaMKII activity and attenuates LTP induction in hippocampal neurons, but does not affect LTD formation. Jung et al (16) reported that GQ1b-treated rats show a marked increase in memory performance in the Y maze test and Morris water maze test (23), suggesting a positive effect of GQ1b on LTP induction in hippocampal CA1 neurons (9,12). In the present study, the d-PDMP-treated mice exhibited both impairment of LTP induction in hippocampal CA1 neurons (Fig.…”
Section: Referencessupporting
confidence: 62%
See 1 more Smart Citation
“…Since activation of CaMKII due to Ca 2+ influx through NMDA receptors is involved in the mechanism of LTP in hippocampal CA1 neurons, but not in the mechanism of LTD, it is possible that inhibition of de novo synthesis of b-pathway gangliosides in d-PDMP-treated mice decreases CaMKII activity and attenuates LTP induction in hippocampal neurons, but does not affect LTD formation. Jung et al (16) reported that GQ1b-treated rats show a marked increase in memory performance in the Y maze test and Morris water maze test (23), suggesting a positive effect of GQ1b on LTP induction in hippocampal CA1 neurons (9,12). In the present study, the d-PDMP-treated mice exhibited both impairment of LTP induction in hippocampal CA1 neurons (Fig.…”
Section: Referencessupporting
confidence: 62%
“…A possible explanation for the different effects of gangliosides on LTP induction and LTD formation might be that b-pathway gangliosides are more effective than a-pathway gangliosides in activating CaMKII in hippocampal neurons (11). In our previous studies, we suggested that it was possible that ganglioside-Ca 2+ complexes may facilitate Ca 2+ influx through NMDA receptors by acting as Ca 2+ donors (9,12). Other studies have suggested the possibility that gangliosides GD1b and GT1b activate CaMKII in hippocampal neurons (7,11).…”
Section: Referencesmentioning
confidence: 85%
“…At Schaffer collateral-CA1 synapses, the tetra-sialoganglioside GQ1b increased the magnitude of LTP much more than did the mono-sialoganglioside GM1 [4, 3335]. Removal of PSA with endo-N, an endosialidase that specifically cleaves α2,8-linked sialic acid, causes impairment of long-term depression as well as LTP.…”
Section: Discussionmentioning
confidence: 99%
“…Many neural functions including memory processing depend on sialic acid in glycoproteins and gangliosides [13]. Sialic acid contained in gangliosides such as the tetra-sialoganglioside GQ1b is crucial for synaptic plasticity and hippocampal memory [4, 5]. The sialic acid polymer (poly sialic acid, PSA), having a large negative charge, attached to neural cell adhesion molecules (NCAM) regulates neural circuit formation in memory and brain development [6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…Ganglioside treatments increased the magnitude of LTP. This increment of LTP was much greater in the case of tetrasialoganglioside GQ1b treatment than in the case of monosialoganglioside GM1 treatment (55)(56)(57)(58). Injection of GQ1b into the rat lateral ventricle improves spatial learning and memory as estimated by the Y-maze and the Morris water maze tests (59).…”
Section: D-4 Role Of Sialidase In Learning and Memorymentioning
confidence: 90%